Spectacular Work: Labor as Entertainment at the World's Columbian Exposition Fairgrounds. Issue 2 (May 2021) - Conti, Meredith
Abstract : Night is falling in the city. Holiday shoppers bustle down the sidewalk, some pausing to gaze at a colorful billboard publicizing the delights of an upcoming exposition. A few crafty rats scamper along a tall wooden fence, stalked by a sinister ratcatcher of the Dickensian mold. Children frolic, fight, and tease one another in front of the fence, the familiar syncopated strains of Tchaikovsky's Nutcracker overture underscoring their exuberant street play. This is not, however, the early 1800s Germany of the upper-class Stahlbaum family. It's 1892 Chicago. In the Joffrey Ballet's 2016 production of The Nutcracker, the story of Clara Stahlbaum's innocent Christmas Eve dalliances with an anthropomorphic nutcracker and their journey to the Land of Sweets becomes the story of Marie, the daughter of a Polish immigrant single mother, whose fantasyland is the future Chicago World's Fair. Marie's mother, we learn, is a hired artist working on the fair's sculptures. Marie, Fritz, and their mother inhabit a wooden shack in the heart of the construction site, surrounded by the skeletal structures that will become the White City's buildings. Drosselmeyer is now "The Great Impresario, " a character of vision and magnetism inspired by the fair's Director of Works Daniel H. Burnham, and Marie's working-class mother transforms in the second act into the embodiment of the fair's golden Statue of the Republic, a less saccharine substitute for the Sugar Plum Fairy. The mutual affection of Mother and The Great Impresario spans both acts, and though the ballet leaves unclear the outcome of their budding romance, in it young Marie sees the promise of her American dream: a contented nuclear family.